Eksplorasi Hubungan Tingkat Pengetahuan Terhadap Kepatuhan Terapi Pasien Hipertensi di UPT Puskesmas Tanjung Batu Kabupaten Karimun - Maulina, Novia; Luthfi, Fitrati Hasanah; Inayatilah, Fidia Rizkiah; muslikh, Faisal akhmal (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2025)
Background: Hypertension is a condition where blood pressure exceeds normal levels (120/80mmHg), with systolic blood pressure above 140 mmHg and diastolic blood pressure above 90mmHg. Termed as the